Slaves to our emotions: Examining the predictive relationship between emotional well-being and academic outcomes. (July 2019) - Geertshuis, Susan A
Few studies have assessed the particular relationships between students' emotional well-being, both positive and negative and their learning. This study followed a cohort of mature students through their first semester at university. Four dimensions of emotional well-being were captured (enthusiasm, contentment, anxiety and depression) at three points in time during the semester. In addition, at the end of the semester, assessments were made of learning behaviours, affect and academic achievement. Emotional well-being fluctuated during the semester and each of the four dimensions exhibited a unique and predictive pattern of relationships with the suite of outcome measures. The findings highlight the importance of emotional well-being in shaping active engagement in learning and in determining affective and academic outcomes. The results are interpreted and the implications for the design of learning environments and teaching practice are outlined.